PENINGKATAN PEMAHAMAN MATA PELAJARAN FIQIH MATERI PUASA MELALUI MODEL PEMBELAJARAN KOOPERATIF - Fauzi Fauzi; Nur Khosiah (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
The research aims to identify an increase in understanding of the Ramadan fasting material by using a cooperative learning model. Studying fiqh at Madrasah Ibtidaiyah is part of the theme of Islamic religious education which aims to train students to know, understand, live and practice Islamic law. Which then becomes the basis for his perspective on life through teaching, learning, trepan education and experience, as well as getting used to everyday life. Class action research (CAR) is research conducted by the teacher in the classroom, which is essentially a series of research activities carried out in cycles to solve a problem until the problem is resolved. The implementation of Teams Games for the fiqh subject of the type of cooperative learning tournament type with Ramadan fasting material for class IV MI Raudlatul Ulum can be applied well. This is evidenced by the results of observations of student activity which also increased from 60% to 80%, in cycles I and II. Based on the development of cycles I and II, the implementation of the cooperative learning model of the team games tournament type was successful and could be perfected. Keywords: Improvement, understanding of fiqh material, and cooperative learning